PENINGKATAN KEMAMPUAN MEMBEDAKAN KONSEP BERAT DAN RINGAN MELALUI MEDIA TIMBANGAN KAYU - Surjanilim Surjanilim; Zahrati Mansoer; Hisyam Abdul Malik (stit-islamic-village, 2021)
The purpose of this research is to improve the ability to distinguish the concept of weight and light learners through the medium of wooden scales, improve the quality of distinguishing concepts of weight and light and motivate the interest of learners in understanding the concept of weight and light in children aged 5-6 years even semester 2020 - 2021 through the media of wooden scales. Success indicators: contains success indicators that reference success in each action, in the form of gradations such as 80-100 (very successful), 60-79 (successful), 40-59 (sufficient), 20-39 (less successful), 0-19 (unsuccessful). If the cognitive ability measured by the minimum completion criteria can be used as a reference. Following the characteristics of class action research, the success of this action is characterized by changes in the direction of improvement related to the learning atmosphere and learning outcomes of students. The purpose of implementation in this study is to improve the ability to distinguish the concept of the light weight of children aged 5-6 years through the medium of wooden scales. The criteria for success in this class action research is the improvement of the completion of learning outcomes of children aged 5-6 years PAUD Cerdas Bangsa Jakarta 75% of the number of children and the average overall value of children is 6, then the research can be said to be successful.